Gantry crane scheduling and storage techniques in rail-road terminals - Chiraag Dinesh Kaidabettu; Ann-Kathrin Lange; Carlos Jahn (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: A rising global container throughput has necessitated the need for more efficient terminals. This work focuses on identifying past developments, important methods, key performance indicators and the future trends, related to the main decision tasks in an inland rail-road terminal. Prime focus is upon day-to-day operations performed on container entry through trains and trucks. Methodology: A comprehensive systematic literature survey is carried out and a classification scheme developed, which is applied to the considered publications. Various techniques used to formulate the model and common solution approaches are identified for the key decision problems. Limitations in the current literature recognized and potential future research directions suggested. Findings: Crane scheduling and storage space allocation are the most concentrated-upon problems. Simulation platforms have been largely used to model the problems and heuristics is the most common approach to solve other models. Time taken and costs involved are sought to be minimized. Originality: In literature, marine container terminals have received greater attention as compared to inland terminals. Due to differing operation procedures, relevant research results from marine cannot be applied directly to railway terminals. Moreover, some of the existing works related to inland were found to disregard certain practical issues rendering them inapplicable for real applications.
urn:nbn:de:gbv:830-882.0162304; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; Port Logistics